TEACHER'S PROFESSIONALIZATION UNDER MARTIAL LAW IN UKRAINE - Svitlana Sysoieva (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article examines the professionalization of teachers in the context of unforeseen situations, in particular the war of the Russian Federation against Ukraine. It is concluded that martial law in Ukraine has affected the priorities of teacher professionalization, as the priorities in the mission and professional activity of the teacher have changed. In the article, the professionalization of a teacher is considered as a process aimed at developing such qualities as adaptability, stress resistance, flexibility, creativity, critical thinking, and provides for such teacher training that provides awareness of a wide range of social needs and challenges to the country, society and the teacher generated by the war, equipping the teacher with knowledge, technology, new competencies that allow him to work, maintain and improve the quality of education in the conditions of uncertainty. Two priorities in the teacher's mission are highlighted: preserving the generation that will further shape the future of Ukraine (professional activity and professional training of teachers should be considered through the prism of preserving the health and lives of children and youth); ensuring the maximum resource of the teacher's own state for professional activity. The challenges to the professionalization of teachers under martial law are analyzed, in particular, the acquisition of new competencies, primarily digital, overcoming the educational losses of students, mastering new forms and methods of teaching in the virtual space (remote, correspondent, mixed, hybrid, mobile, etc.), mastering the technologies of creative development of students, in particular, the expansion of educational and creative tasks to increase the psychorehabilitation effect of the educational process.